Dynamics and Energy Management of Electric Vehicles - Van Schalkwyk, Daniel Jacobus (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2007.